Hybrid cluster analysis of customer segmentation of sea transportation users - Bambang Eka Cahyana; Umar Nimran; Hamidah Nayati Utami; Mohammad Iqbal (Journal of Economics Finance and Administrative Science, 2020)
Purpose – The purpose of this study is to apply hybrid cluster analysis in classifying PT Pelindo I customers based on the level of customer satisfaction with passenger services of PT Pelindo I. Design/methodology/approach – Hybrid cluster analysis is a combination of hierarchical and non-hierarchical cluster analysis. This hybrid cluster analysis appears to optimize the advantages of hierarchical and non-hierarchical methods simultaneously to obtain optimal grouping. Hybrid cluster analysis itself has high flexibility because it can combine all hierarchical and non-hierarchical methods without any limits in the order of analysis used. Findings – The results showed that 72% of PT Pelindo I customers felt PT Pelindo I service was special, while the remaining 28% felt PT Pelindo I service was good. Originality/value – In total, 117 customers of PT Pelindo I were involved in a study using the non-probability sampling method.